Improving the anti‐inflammatory effect of serum eye drops using allogeneic serum permissive for regulatory T cell induction. (14th July 2015) - Stenwall, Per‐Anton; Bergström, Marcus; Seiron, Peter; Sellberg, Felix; Olsson, Tobias; Knutson, Folke; Berglund, David
Abstract Purpose To investigate the cytokine composition and anti‐inflammatory effects of allogeneic serum preparations for improved use as serum eye drops. Methods Serum of 15 healthy blood donors was extensively screened for cytokines, including IL‐1β, IL‐2, IL‐4, IL‐5, IL‐6, IL‐9, IL‐10, IL‐12p70, IL‐13, IL‐15, 1L‐17A, E and F, IL‐21, IL‐22, IL‐23, IL‐27, IL‐28A, IL‐31, IL‐33, granulocyte macrophage colony‐stimulating factor (GM‐CSF), chemokine ligand 20 (CCL20), tumour necrosis factor (TNF)‐α and TNF‐β, interferon (IFN)‐γ and transforming growth factor (TGF)‐β. The levels of cytokines were assessed before and after heat‐induced inactivation. Individual serum preparations were tested for their anti‐inflammatory effect using an in vitro test to differentiate effector T lymphocytes into anti‐inflammatory regulatory T cells. Results The anti‐inflammatory cytokine TGF‐β was readily detected in the serum of all blood donors and was only modestly affected by heat‐induced inactivation. Serum containing high amounts of TGF‐β was more effective at inducing anti‐inflammatory regulatory T cells. The serum of one healthy blood donor displayed high levels of inflammatory cytokines. Conclusion We propose that serum used as eye drops is screened for its cytokine content, making it possible to correlate the composition to the clinical outcome. Based on the findings in this study, tailored serum eye drops produced from allogeneic donors may provide increased anti‐inflammatory effects. This may be superior to autologous serum eye drops, which in many cases are retrieved from patients with inflammatory diseases.